The Effectiveness of the Glasser Learning Model Based on Local Wisdom on Speaking Skills State 1 Galang SMA Students - Tambunan, Marlina Agkris; Hutabarat, Novra Melisa P (Future Science / FSH-PH Publications, 2022)
The purpose of this study is to describe the effectiveness of the model glasser learning based on local wisdom on the speaking skills of SMA Negeri 1 Galang students. This type of research is a quasi experimental type with the design of The One-Group Pretest-Posttest. Pretest observations were carried out on a group of respondents who were then given treatment. Researchers will compare the effectiveness of the learning model on the results before and after being given treatment. The sampling used in this study is a group sample (Cluster Sampling) because this sampling does not interfere with the teaching and learning process in the classroom. Therefore, the sample of this study involved 36 students in class XA4. The results in this study were at the pretest or before the implementation of the learning model, it reached an average of 54.61 in the less category. Skill assessment results students' speaking at the posttest or after the implementation of the learning model there was an increase reaching 74.44 in the good category, therefore based on the results of the prettest and posttest there were differences in the results of the speaking skills of class X students of SMA Negeri 1 Galang before and after using the glasser learning model based on local wisdom. Based on the data analysis of students' speaking skills at the pretest and posttest, it was obtained t count = 12.01 at a significant level of 0.05 (95% confidence level) at df = 35 obtained t table = 2.031. Then t count = 12.01 > t table = 2.0315, so it can be concluded that H 0 is rejected and Ha is accepted, glasser model based wisdom effective in improving skills speak SMA Negeri 1 Galang students.